Enhancement of Pineapple Industrial Waste Delignification Through the Effect of Microwave Irradiation Duration with Alkali Assistance. - Rhea Alvita, Livia; Elsyana, Vida; Hidayat, Rahmat; Saputra, Anggi; Variyana, Yeni; Rustiawan Jody, Rafli (Indonesian Journal of Chemical Analysis (IJCA), 2026)
Delignification is an important step for removing lignin, increasing the accessibility of cellulose and hemicellulose for various industrial applications. This study investigated the effect of microwave irradiation duration on the alkaline-assisted delignification of pineapple peel waste using a Completely Randomized Design (CRD) with irradiation times of 0, 15, 30, and 45 minutes at a constant power of 45 W. Compositional analysis was performed using the Chesson–Datta method, while structural and chemical modifications were evaluated through Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The results indicated that increasing irradiation time significantly improved delignification efficiency (P < 0.05), with the highest lignin reduction of 57.6% achieved at 45 minutes, accompanied by increases in cellulose and hemicellulose contents of 62.79% and 55.8%, respectively. FTIR spectra confirmed the removal of lignin through the reduction of characteristic functional group intensities. Moreover, SEM analysis revealed pronounced structural disruption, increased surface irregularity, and enhanced porosity after treatment, indicating effective breakdown of the lignocellulosic matrix and improved exposure of cellulose fibers. These findings demonstrate that microwave-assisted alkaline treatment is a promising approach for enhancing the valorization of pineapple industry waste.